Functional genome analysis reveals that serine carboxypeptidase Bd-SCP10 mediates vegetative growth, pathogenicity, and stress tolerance in Botryosphaeria dothidea - Umer, Muhammad; Anwar, Naureen; Mubeen, Mustansar; Li, Yun; Alsyaad, Khalid M.; Ahmed, Ahmed Ezzat; Liu, Pingwu (Frontiers in Plant Science, 2025)
IntroductionBotryosphaeria dothidea (B. dothidea) is a catastrophic fungal pathogen that threatens fruit production worldwide. Secreted peptidases like serine carboxypeptidases (SCPs) are well known to be involved in fungal virulence, but their role in B. dothidea is unknown.MethodologyHere, we identified and functionally characterized Bd-SCP10, a homolog of SCPs found in B. dothidea, which is a member of the S10 family, using a split marker strategy for gene knockout and complementation.ResultsMutants exhibited substantial phenotypic changes, including reduced radial growth and compromised biomass production, as well as altered pathogenicity and stress tolerance in response to multiple stress conditions. In contrast, complementation restored these traits, suggesting a functional role of Bd-SCP10. Particularly, Bd-SCP10 contributes to maintaining growth, cell wall integrity and adaptation to host-induced stresses, highlighting its involvement in fungal survival and pathogenicity.DiscussionThis study provides the first functional evidence that secreted peptidases in B. dothidea are a key factor in vegetative growth, pathogenicity, and stress tolerance. The identification and functional characterization of Bd-SCP10 led us to believe that it is a promising molecular target for eco-friendly strategies to manage diseases caused by B. dothidea and related pathogens.